The socio-economic impacts of the COVID-19 mitigation measures and vulnerabilities in Singapore - Daly, Patrick (2025)
Starting in early 2020, countries around the world imposed mitigation measures to reduce transmission of COVID-19 including social distancing; closing public transport, schools, and non-essential businesses; enhanced hygiene; face masks; temperature monitoring; quarantining; and contact tracing. These mitigation measures helped reduce loss of life, but also disrupted the lives of billions of people. Here we assess whether mitigation measures used to manage a disaster can also have negative impacts that disproportionately burden vulnerable sub-sets of a population. We use data from a survey of Singaporean citizens and permanent residents during the lockdown period between April and July 2020 to evaluate the social and economic impacts of Singapore's COVID-19 mitigation measures. Our results show that over 60 % of the population experienced negative impacts on their social lives and 40 % on household economics. Bayesian Hierarchical Logistic Regress reveals that the negative economic impacts of the mitigation measures were partly influenced by socio-economic and demographic factors that align with underlying societal vulnerabilities. Our findings suggest that when dealing with large-scale crisis' such as COVID-19, slow-onset disasters, and climate change, some of the burdens of mitigation measure can constitute a crisis in their own right which could disproportionately impact vulnerable segments of the population.